The Effect of Clay/Multiwall Carbon Nanotube Hybrid Fillers on the Properties of Elastomer Nanocomposites - Sung Ho Song (International Journal of Polymer Science)
The hybrid fillers of 1D multiwalled carbon nanotubes (MWNT) and 2D montmorillonite (MMT) have led to excellent physical and chemical properties in high performance elastomer nanocomposites. In this study, the hybridization of PDDA (polydiallyldimethylammonium chloride) functionalized MWNT (P-MWNT) and hydroxyl-functionalized MMT (H-MMT) was prepared by the electrostatic interaction between the positive charge on the MWNT and the negative charge on the MMT using a simple solution mixing process. Also, a styrene-butadiene rubber (SBR) nanocomposite containing the hybrid nanofillers was prepared to improve the dispersion of nanofillers with SBR latex. The SBR nanocomposites with the hybrid nanofillers exhibited outstanding mechanical properties including modulus, tensile strength, and elongation at break, due to the enhanced interfacial bonding with the elastomer matrix. Furthermore, the hybrid nanofillers in the SBR matrix showed superior thermal and electrical properties and gas barrier performance at low loadings. The synergistic effects of the SBR produced by the hybridized nanofillers will open up new opportunities for elastomer composites with high performance.